RETRACTED: Analysis The Effect Of Profitability, Liquidity, Company Size, And Sales Growth On Capital Structure - Rahmat Fauzi; elwisam elwisam; Kumba Digdowiseiso (Journal of Social Science)
This study aims to determine and analyze the influence between Profitability, Liquidity, Company Size, and Sales Growth on Capital Structure in public companies in the property and real estate sub-sector on the Indonesia Stock Exchange for the period 2011-2015. In this study, four variables were taken that allegedly affect Capital Structure, namely Profitability, Liquidity, Company Size, and Sales Growth with multiple linear regression analysis equations using the Stepwise method, classical assumption testing consisting of normality tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests using the Statistical Product for Social Science (SPSS) program version 22.0 for windows and Microsoft Excel 2016. The sample of companies was taken as many as 33 companies from 49 populations of property and real estate sub-sector companies on the Indonesia Stock Exchange. The results of this study show that partially, Liquidity, and Company Size have a significant influence on Capital Structure. Meanwhile, in terms of model feasibility there is a significant influence between Liquidity, Company Size, and Sales Growth on Capital Structure. Should be able to pay more attention to the movement or change of Capital Structure based on the variables of Profitability, Liquidity, Company Size, and Sales Growth. Because these variables can affect the rise or fall of the Capital Structure in public companies, propert and real estate sub-sectors.